2013
DOI: 10.1111/j.1755-6686.2013.12040.x
|View full text |Cite
|
Sign up to set email alerts
|

The Oral Health Status of Patients With Renal Disease in Central India: A Preliminary Study

Abstract: This study provides evidence for greater periodontal disease amongst patients with renal disease as compared with healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 13 publications
(12 reference statements)
2
24
0
4
Order By: Relevance
“…Table summarizes the characteristics of the studies that evaluated dental caries among individuals with CKD compared to non‐CKD individuals. Twenty studies recruited participants with CKD from specialized centers (Almeida et al, ; Al‐Nowaiser et al, ; Andrade et al, ; Bayraktar et al, ; Caliento et al, ; Cengiz et al, ; Chamani et al, ; Davidovich, Schwarz, et al, ; Ertuğrul et al, ; Jaffe et al, ; Kanjanabuch et al, ; Limeres et al, ; Martins et al, ; Pakpour et al, ; Schmalz et al, ; Sobrado Marinho et al, ; Tadakamadla et al, ; Teratani et al, ; Tiwari et al, ; Wolff et al, ). One study sought participants in a textile industry (Garcez et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Table summarizes the characteristics of the studies that evaluated dental caries among individuals with CKD compared to non‐CKD individuals. Twenty studies recruited participants with CKD from specialized centers (Almeida et al, ; Al‐Nowaiser et al, ; Andrade et al, ; Bayraktar et al, ; Caliento et al, ; Cengiz et al, ; Chamani et al, ; Davidovich, Schwarz, et al, ; Ertuğrul et al, ; Jaffe et al, ; Kanjanabuch et al, ; Limeres et al, ; Martins et al, ; Pakpour et al, ; Schmalz et al, ; Sobrado Marinho et al, ; Tadakamadla et al, ; Teratani et al, ; Tiwari et al, ; Wolff et al, ). One study sought participants in a textile industry (Garcez et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…; Tiwari et al . ). Our study also demonstrated that all the patients in our haemodialysis unit had periodontal disease, and more than half were brushing their teeth less than twice a day.…”
Section: Discussionmentioning
confidence: 97%
“…; Tiwari et al . ) and it is thought that CKD and periodontitis could affect the course of each other. While periodontitis could facilitate the development of chronic inflammation in this patient population (Wasserman et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…[6] A higher percentage of periodontal disease among patients with renal disease was noted when these patients were compared with healthy individuals. [7] The prevalence and severity of chronic periodontitis in the previous cohort of chronic kidney disease patients was markedly higher than it was in a geographically matched control population in Europe. [38] In another report, poor oral health, which includes chronic periodontitis, was a common finding in patients undergoing hemodialysis, and chronic periodontitis was considered a continuous, reversible source of inflammation and this has a potential impact on mortality in patients undergoing hemodialysis.…”
Section: Discussionmentioning
confidence: 99%
“…[6] The incidence of periodontal disease (bleeding and calculus) was significantly higher among people with renal disease than among controls. [7] Recently, it was reported that periodontitis was associated with increased prevalence of inflammatory markers in end-stage renal disease patients. [8] Recent epidemiological studies have suggested that periodontitis is a major risk factor for renal failure.…”
Section: Introductionmentioning
confidence: 99%